Economic evaluation of woodchip-derived bio-adsorbent production: a case study using a self-sustained pilot-scale pool-type carbonization reactor - Samsudin, Mohd Hafif; Mohd Yusoff, Mohd Zulkhairi; Roslan, Ahmad Muhaimin; Hassan, Mohd Ali; Idris, Juferi; Ahmad Farid, Mohammed Abdillah; Yoshihito, Shirai (Springer, 2025)
This study presents a comprehensive techno-economic assessment of woodchip-derived bio-adsorbent production using a self-sustained, pool-type carbonization reactor designed for decentralized and low-energy deployment. The reactor operates at 300–700 °C with a heating rate of 5–7 °C/min, processing 3–5 tonnes of biomass per 7-day batch and yielding up to 1 tonne of biochar (20 wt.%), with an annual production capacity of 48 tonnes. The biochar exhibited strong adsorptive performance in landfill leachate treatment, achieving removal efficiencies of 73.2% for COD, 97.3% for total Kjeldahl nitrogen, and 768.8% for ammoniacal nitrogen, surpassing other biomass-derived chars. Physicochemical characterization showed a substantial increase in BET surface area from 0.91 to 232.1 m2/g and a reduction in average pore size from 324.1 to 15.4 nm, accompanied by a fixed carbon increase from 1.1% to 72.4%, indicating enhanced mesoporosity and aromaticity. An economic assessment based on a 10-year projection yielded a unit production cost of USD 394 per tonne, a net present value (NPV) of USD 36,905, an internal rate of return (IRR) of 94.6%, and a rate of return (ROR) of 92.5%, outperforming most comparable systems that report IRRs between 9 and 55% under higher capital and energy inputs. This study demonstrates that the integration of low-cost infrastructure, self-sustained operation establishes this pyrolysis system as a practical and scalable solution for circular bioeconomy implementation, particularly in resource-constrained and rural settings.